Applying generalizability theory to examine assessments of subjective cognitive complaints: whose reports should we rely on – participant versus informant?. (13th December 2022) - Truong, Q. C.; Choo, C.; Numbers, K.; Merkin, A. G.; Brodaty, H.; Kochan, N. A.; Sachdev, P. S.; Feigin, V. L.; Medvedev, O. N.
ABSTRACT: Objectives: This study aimed to apply the generalizability theory (G-theory) to investigate dynamic and enduring patterns of subjective cognitive complaints (SCC), and reliability of two widely used SCC assessment tools. Design: G-theory was applied to assessment scales using longitudinal measurement design with five assessments spanning 10 years of follow-up. Setting: Community-dwelling older adults aged 70–90 years and their informants, living in Sydney, Australia, participated in the longitudinal Sydney Memory and Ageing Study. Participants: The sample included 232 participants aged 70 years and older, and 232 associated informants. Participants were predominantly White Europeans (97.8%). The sample of informants included 76 males (32.8%), 153 females (65.9%), and their age ranged from 27 to 86 years, with a mean age of 61.3 years (SD = 14.38). Measurements: The Memory Complaint Questionnaire (MAC-Q) and the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE). Results: The IQCODE demonstrated strong reliability in measuring enduring patterns of SCC with G = 0.86. Marginally acceptable reliability of the 6-item MAC-Q (G = 0.77–0.80) was optimized by removing one item resulting in G = 0.80–0.81. Most items of both assessments were measuring enduring SCC with exception of one dynamic MAC-Q item. The IQCODE significantly predicted global cognition scores and risk of dementia incident across all occasions, while MAC-Q scores were only significant predictors on some occasions. Conclusions: While both informants' (IQCODE) and self-reported (MAC-Q) SCC scores were generalizable across sample population and occasions, self-reported (MAC-Q) scores may be less accurate in predicting cognitive ability and diagnosis of each individual.